A new constitutive model on biaxial tensile behavior of architectural fabrics. (July 2020) - Gao, Chengjun; Chen, Wujun; Hu, Jianhui; Zhao, Bing
Abstract: Accurate and concise constitutive model of biaxial tensile behavior is urgently needed for the analysis of complex membrane structure engineering. A new constitutive model is developed to describe the tensile behaviors of coated fabrics from pre-tension to breaking. The shrinkage curve is employed for the first time and stress-ratio dependence coefficient (SDC) is proposed to represent the proportion of elongation and shrinkage in biaxial monotonic tensile test. The deformation of cruciform specimen is considered as the result of the coupling effect of biaxial tension and Poisson effect. Excellent fitting results were obtained between the data points of biaxial tensile test and stress-stress-strain response surface, which R-squares of both warp and weft response surface were 0.995. Highlights: The shrinkage curves was employed for the first time. Stress-ratio dependence coefficient (SDC) was proposed to represent the proportion of elongation and shrinkage in different stress ratios. Excellent fitting results were obtained between the data points of biaxial tensile test and stress-stress-strain response surface, and R-squares of both warp and weft response surface were 0.995.